2021
DOI: 10.1016/j.wroa.2021.100117
|View full text |Cite
|
Sign up to set email alerts
|

Periodic chemical cleaning with urea: disintegration of biofilms and reduction of key biofilm-forming bacteria from reverse osmosis membranes

Abstract: Highlights Multiple chemical cleaning cycles were applied to biofouled RO membranes. Improved membrane performance with periodic urea cleaning. Enhanced removal efficiency of the surface fouling layer post urea treatment. Urea cleaning does not select for resistant microbial communities in the biofilm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…Since urea is a protein denaturant, its effect on biofilm may depend on EPS composition and protein content. Past studies have demonstrated biofilm weakening and enhanced biofilm removal ,, upon treatment with urea at concentrations ranging from 0.2 to 2 M. For example, Chen & Stewart (2000) reported 73% biofilm protein removal from binary biofilms of P. aeruginosa and Klebsiella pneumonia using 200 mM urea .…”
Section: Discussionmentioning
confidence: 99%
“…Since urea is a protein denaturant, its effect on biofilm may depend on EPS composition and protein content. Past studies have demonstrated biofilm weakening and enhanced biofilm removal ,, upon treatment with urea at concentrations ranging from 0.2 to 2 M. For example, Chen & Stewart (2000) reported 73% biofilm protein removal from binary biofilms of P. aeruginosa and Klebsiella pneumonia using 200 mM urea .…”
Section: Discussionmentioning
confidence: 99%